Surface treatments with TiO2 nanostructures for bonding to zirconia materials as an alternative to conventional airborne-particle abrasion of the surface - Constantino Fernandes-Neto; Erika Bronze-Uhle; Leonardo Francisco Gonçalves Dias; Fabio Antonio Piola Rizzante; Paulo Noronha Lisboa-Filho; Adilson Yoshio Furuse (Next Nanotechnology)
Zirconia has become a popular choice for indirect restorations; however, adhesion to this material remains a challenge. The present study aimed to evaluate surface characteristics and bond strength to tetragonal Y-TZP and cubic Y-PSZ zirconia submitted to experimental surface treatments. Specimens of Y-TZP (T) and Y-PSZ (P) were prepared and divided into groups: Tf-A) thin TiO2 film functionalized with 3-(aminopropyl)trimethoxysilane (APTMS); Tf) thin TiO2 film; MNt-A) manual application of TiO2 nanotubes with APTMS; MNt) manual application of TiO2 nanotubes; VNt-A) vacuum application of TiO2 nanotubes with APTMS; VNt) vacuum application of TiO2 nanotubes; C) control with Al2O3 sandblasting. Characterization with x-ray photoelectron spectroscopy (XPS) and scanning electron microscopy (SEM) was done. Bond strength was evaluated by microshear bond strength (µSBS). Data were analyzed by two-way ANOVA and Tukey’s HSD tests (α = 0.05). XPS showed signals for elements O 1 s, Ti 2p, and Zr 3d 5/2. In addition, high-resolution demonstrated Ti-O-Si and Zr-O-Si bonding for treatments with TiO2 and APTMS for T-Tf-A/P-Tf-A. SEM presented a homogeneous film for T-Tf/T-Tf-A/P-Tf/P-Tf-A and cluster formations for all nanotube groups. Control groups for both Y-TZP and Y-PSZ showed clear surfaces. No differences of µSBS were seen between experimental surface treatments and the controls, except for T-MNt-A/T-VNt-A/P-MNt-A/P-VNt-A, which showed the lowest mean µSBS and highest incidence of pre-test failures. Surface treatments with TiO2 nanostructures were effective in modifying the surface of both zirconia materials evaluated, providing strong covalent bonds, changes to the surface topology, and shear bond strength comparable to conventional sandblasting protocols.